A conceptual model to understand the drivers of change in tropical wetlands: a comparative assessment in India and Brazil - Sarkar, Priyanka; Salami, Mercy; Githiora, Yvonne; Vieira, Raísa; Navarro, Alma; Clavijo, Diana; Padgurschi, Maíra (Biota Neotropica, 2020)
Abstract: Tropical wetlands are amongst the most biodiverse ecosystems on Earth and have immense socio-ecological value. However, tropical wetlands are considered exploitable resources and continue to be drained and converted to other “productive” uses. It is therefore urgent to identify and understand the interactions between various drivers of change triggering degradation of such wetlands. In the present study, we systematically reviewed and analyzed the existing literature on wetlands in two tropical countries namely India and Brazil with special reference to inland wetlands, and proposed a conceptual model illustrating the intricate linkages of such wetlands with different drivers of change. We also developed the Nature Futures’ Framework to depict the diverse values of inland wetlands contributing to human wellbeing in the two tropical countries. Findings revealed similar drivers of change triggering the degradation of Indian and Brazilian wetlands. These include changes in climate & land use, population growth, poor land governance due to weak policies, besides other anthropogenic activities such as deforestation, and overexploitation of wetland resources. Among these, land-use change such as agriculture intensification and infrastructure development were the major direct drivers; whereas, institutional and governance factors such as the absence of concrete policy measures were the major indirect drivers threatening the inland wetlands in India and Brazil. Results also revealed some contrasting drivers of change such as illegal human settlements, and land grabbing by the brick industry for Indian wetlands; while, gold mining and intensification of bovine systems for Brazilian wetlands. Our paper also provides an insight into the status of wetland conservation in India and Brazil. We recommend the promotion of community-based conservation practices while adopting sustainable livelihood strategies by the local people for the conservation and wise use of inland wetlands in India and Brazil. The arguments raised in the paper have the potential to assist the stakeholders and/or decision-makers towards implementing sustainable management strategies for inland wetlands in the two countries, and tropical wetlands in general.